Effectiveness of Counseling and Education Using The Maternal and Child Health (MCH) Handbook on Nutritional Knowledge of Pregnant Women With Chronic Energy Deficiency - Marlita Marlita; Yusnaini Yusnaini; Nurdahliana Nurdahliana; Cut Yuniwati Cut Yuniwati; Lia Lajuna Lia Lajuna (Poltekkes Kemenkes Semarang, 2026)
Background:Chronic Energy Deficiency (CED) in pregnant women remains a significant nutritional issue, posing risks to both maternal and fetal health. One of the contributing factors is the lack of knowledge regarding proper nutritional intake during pregnancy. Counseling and education using the Maternal and Child Health (MCH) Handbook is expected to improve pregnant women’s nutritional knowledge.Objective:To determine the effectiveness of counseling and education using the MCH Handbook in improving knowledge of nutritional needs among pregnant women with CED in the working area of Montasik Public Health Center, Aceh Besar.Methods:This study employed a quasi-experimental design with a two-group pretest-posttest model. The sample consisted of 30 pregnant women with CED, divided into two groups: one receiving health education and the other receiving counseling. Data were collected using pretest and posttest questionnaires and analyzed using paired t-tests.Results:The paired t-test showed a significant increase in knowledge in both groups. The education group had a p-value of 0.001 and the counseling group had a p-value of 0.000 (p < 0.05), indicating that both methods were effective in enhancing nutritional knowledge among pregnant women with CED. The results of the study also indicate that counseling was proven to be more effective, with a p-value of 0.002.Conclusion:Counseling and education using the Maternal and Child Health (MCH) Handbook (Buku KIA) have been proven effective in increasing knowledge about fulfilling the nutritional needs of pregnant women with Chronic Energy Deficiency (CED). However, the results of the study indicate that direct counseling is more effective compared to education using the MCH Handbook.